The mediating effect of life satisfaction between daily living abilities and depressive symptoms in the Chinese older people: evidence from CHARLS 2020 - Mingsheng Liao; Xuesi Zhang; Zhiquan Xie; Limei Li; Liqin Zou (Frontiers Media S.A., 2024)
BackgroundDepressive symptoms represent a significant public health challenge, impacting the mental well-being of older adults. Despite this, the understanding of how activities of daily living (ADL) abilities correlate with life satisfaction and depressive symptoms among older Chinese adults remains limited.AimsThis study aims to investigate the relationship between ADL and depressive symptoms in older people Chinese individuals, with a specific focus on examining the mediating role of life satisfaction within this context.MethodsThe study utilized data from the China Health and Retirement Longitudinal Study (CHARLS) collected in 2020. A cohort of 8,343 individuals aged 60 years and above was included. The analysis was conducted using STATA 17.0 and SPSS 26.0, employing descriptive statistics, chi-square tests, Pearson correlations, and mediation analysis using the percentile Bootstrap method with 5,000 resamples to explore the interrelations among ADL, life satisfaction, and depressive symptoms.ResultsADL is positively correlated with life satisfaction (r = 0.129, p < 0.01) and negatively correlated with depressive symptoms (r = −0.313, p < 0.01). Additionally, life satisfaction and depressive symptoms are negatively correlated with each other (r = −0.360, p < 0.01). In the model of the mediating effect, ADL directly, significantly and negatively predicts depressive symptoms in the Chinese older people (β = −0.193, t = −17.827, p < 0.001). After incorporating life satisfaction into the regression equation, the direct predictive effect of ADL on depressive symptoms remains significant (β = −0.177, t = −17.099, p < 0.001); furthermore, ADL has a significant positive predictive effect on life satisfaction (β = 0.007, t = 4.959, p < 0.001) and life satisfaction significantly negatively predicts depressive symptoms (β = −2.235, t = −27.799, p < 0.001). Furthermore, the direct effect of ADL on depressive symptoms (−0.177) and its mediating effect (−0.016) account for 91.71% and 8.29% of the total effect (−0.193), respectively.ConclusionADL is inversely associated with the risk of depressive symptoms among older people Chinese individuals, with life satisfaction serving as a significant mediator in this relationship. Interventions aimed at improving life satisfaction in older people individuals with ADL impairments may effectively reduce or prevent the onset of depressive symptoms.